INFORMM USM WILL ORGANISE TALKS ON DIAGNOSING DENGUE IN TIMES OF MASSIVE CHIKUNGUNYA AND ZIKA OUTBREAKS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
The Institute for Research in Molecular Medicine (INFORMM), Universiti Sains Malaysia would like to cordially invite all experts to talks by the Project Leader at NovaTec Immundiagnostica GmbH, Dr. Andreas Latz, at INFORMM Auditorium, USM Main Campus on 22nd April 2016 (Friday).